High-Risk Lineages of Hybrid Plasmids Carrying Virulence and Carbapenemase Genes - Valeria V. Shapovalova; Polina S. Chulkova; Vladimir A. Ageevets; Varvara Nurmukanova; Irina V. Verentsova; Asya A. Girina; Irina N. Protasova; Victoria S. Bezbido; Victor I. Sergevnin; Irina V. Feldblum; Larisa G. Kudryavtseva; Sergey N. Sharafan; et al. (Antibiotics)
Background/Objectives: Carbapenem-resistant Enterobacterales (CRE) are a global health threat due to their high morbidity and mortality rates and limited treatment options. This study examines the plasmid-mediated transmission of virulence and antibiotic resistance determinants in carbapenem-resistant Klebsiella pneumoniae (Kpn) and Escherichia coli (E. coli) isolated from Russian hospitals. Methods: We performed short- and long-read whole-genome sequencing of 53 clinical isolates (48 Kpn and 5 E. coli) attributed to 15 genetic lineages and collected from 21 hospitals across nine Russian cities between 2016 and 2022. Results: The plasmid analysis identified 18 clusters that showed high concordance with replicon typing, with all clusters having a major replicon type. The majority of plasmids in the IncHI1B(pNDM-MAR)/IncFIB(pNDM-Mar)-like cluster (79.16%) carried both antibiotic resistance genes (e.g., blaNDM-1 and blaOXA-48) and virulence factors (VFs) such as siderophore genes. We hypothesized that hybrid plasmids could play a critical role in the dissemination of antibiotic resistance genes and VFs. Comparative analyses with global plasmid databases revealed high-risk lineages of hybrid plasmids that are predominantly spread throughout Russia at present. Conclusions: Our findings underscore the importance of monitoring plasmid backbones for clinical management, surveillance, and infection control activities.